Atypically large well-differentiated hepatocellular carcinoma with extensive fatty metamorphosis: Report of a Case - Utsunomiya, Tohru; Kanamoto, Mami; Morine, Yuji; Asanoma, Michihito; Shimada, Mitsuo; Iwahashi, Shuichi; Ishikawa, Daichi; Yamada, Shinichiro; Ikemoto, Tetsuya; Mori, Hiroki; Imura, Satoru; Arakawa, Yusuke (The Journal of Medical Investigation, 2013)
A large well-differentiated hepatocellular carcinoma (HCC) with fatty change is rare, and to date only a few cases have been reported. Herein, we present a 68-year-old man who developed a well-differentiated HCC with extensive fatty metamorphosis. The patient was referred to our institute because of a rapidly growing tumor in the left lobe of the liver. Ultrasonography showed a hyperechoic lesion with a peripheral hypoechoic area. Dynamic contrast-enhanced computed tomography (CT) scan in all three phases revealed the tumor which showed diffuse low attenuation with internal irregular enhancement. He underwent left lateral segmentectomy at the liver. Histological diagnosis confirmed well-differentiated HCC and the surrounding non-cancerous area was diagnosed as non-alcoholic steatohepatitis. The patient is still alive without recurrence after 17 months of follow-up. J. Med. Invest. 60: 267-271, August, 2013